Apakah Reputasi Perusahaan Menghasilkan Laba Yang Berkualitas Di Indonesia? - Agung Prasetyo Nugroho Wicaksono (Pusat P2M Politeknik Negeri Batam, 2020)
This study examines how the influence of a company's reputation on the quality of earnings generated from financial statements. The research data used are secondary data in the form of annual reports and financial reports from the Indonesia Stock Exchange within a period of 3 years (2016 - 2018). The research sample is non-financial sector companies listed on the Indonesia Stock Exchange. The main variable in this study is the company's reputation as an independent variable and earnings quality as the dependent variable. The control variables used in this study are asset growth, company size and ROA. Panel data regression was used as a tool to test the hypotheses of this study.